2005
DOI: 10.1063/1.1994942
|View full text |Cite
|
Sign up to set email alerts
|

Phase-separated Al–Si thin films

Abstract: Phase-separated Al–Si films composed of Al nanocylinders embedded in an amorphous-Si matrix have been prepared by a sputtering method. By controlling the deposition rate, substrate temperature, and film composition, the average diameter of the Al cylinders can be varied systematically from less than 5to13nm with a cylinder density ranging from 1015 to in excess of 1016cylindersm−2. A three-dimensional simulation of phase separation in binary thin films was performed using a modified Cahn-Hilliard [J. Chem. Phy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 13 publications
3
30
0
Order By: Relevance
“…1. Our previous simulation results revealed that an increase in surface diffusion length could increase the cylinder's average diameter to some extent because it promotes phase separation [11]. The surface migration of Al and Si atoms increased due to Ar ion bombardment caused by applying bias voltage.…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…1. Our previous simulation results revealed that an increase in surface diffusion length could increase the cylinder's average diameter to some extent because it promotes phase separation [11]. The surface migration of Al and Si atoms increased due to Ar ion bombardment caused by applying bias voltage.…”
Section: Resultsmentioning
confidence: 97%
“…According to our previous simulation results using a modified Cahn-Hilliard spinodal decomposition equation, the surface diffusion length and film composition ratio are important factors that determine the morphology of phaseseparated binary film [11]. The surface diffusion length is supposed to be controlled by the bias voltage applied to the substrate and the substrate temperature.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…1͑a͔͒. 7,8 The deposition time is controlled to prepare films of desired thickness. After fabricating the phase separated Al-Si films, the Al cylinders are removed by etching in a 98% sulfuric acid solution for 24 h at room temperature.…”
Section: Characterization Of Nanoporous Si Thin Films Obtained By Al-mentioning
confidence: 99%